Early handling and repeated cross-fostering have opposite effect on mouse emotionality - Luchetti, Alessandra; Oddi, Diego; Lampis, Valentina; Centofante, Eleonora; Felsani, Armando; Battaglia, Marco; D’Amato, Francesca R. (Frontiers in Behavioral Neuroscience, 2015)
Early life events have a crucial role in programming the individual phenotype and exposure to traumatic experiences during infancy can increase later risk for a variety of neuropsychiatric conditions, including mood and anxiety disorders. Animal models of postnatal stress have been developed in rodents to explore molecular mechanisms responsible for the observed short and long lasting neurobiological effects of such manipulations. The main aim of this study was to compare the behavioral and hormonal phenotype of young and adult animals exposed to different postnatal treatments. Outbred mice were exposed to i) the classical Handling protocol (H: 15 min-day of separation from the mother from day 1 to 14 of life) or to ii) a Repeated Cross-Fostering protocol (RCF: adoption of litters from day 1 to 4 of life by different dams). Handled mice received more maternal care in infancy and showed the already described reduced emotionality at adulthood. Repeated cross fostered animals did not differ for maternal care received, but showed enhanced sensitivity to separation from the mother in infancy and altered respiratory response to 6%CO2 in breathing air in comparison with controls. Abnormal respiratory responses to hypercapnia are commonly found among humans with panic disorders, and point to RCF-induced instability of the early environment as a valid developmental model for panic disorder. The comparisons between short- and long-term effects of postnatal handling vs. RCF indicate that different types of early adversities are associated with different behavioral profiles, and evoke psychopathologies that can be distinguished according to the neurobiological systems disrupted by early-life manipulations.